Integrating Kafaah Nasabiyah in Islamic Family Education: Lessons from Ibn Qudamah and Ibn Hazm in the Indonesian Context - Jamal, Jamal; Israqunnajah, Israqunnajah; Zenrif, M. Fauzan; Al-Turki, Usamah (Madania: Jurnal Kajian Keislaman, 2025)
This study examines the extent to which kafaah nasabiyah can serve as a solution to strengthen household resilience amid rising divorce rates caused by social, economic, and cultural disparities in an increasingly heterogeneous society. The research employs a qualitative approach with a library research design. Primary data is sourced from the works of Ibn Qudamah, such as al-Mughni, and Ibn Hazm through al-Muhalla, supplemented by secondary data from classical and contemporary fiqh literature, Islamic legal documents, and jurisprudential analyses in Indonesia. The data analysis technique involves a descriptive-analytical method with a comparative approach to identify commonalities and differences in the thoughts of both scholars and their implications for the practice of Islamic law in Indonesia. The findings reveal that kafaah nasabiyah holds historical and sociological significance in maintaining household stability. Ibn Qudamah supports the concept as a means to prevent disharmony caused by social disparities, while Ibn Hazm rejects it, arguing that Islam does not impose lineage-based restrictions on marriage. Both in the scope of Islamic boarding schools, madrasas, or premarital education programs, Ibn Qudamah’s perspective is more widely adopted in social practices, particularly in communities that continue to uphold lineage-based stratification when selecting marriage partners. However, this study also finds that the primary causes of divorce in Indonesia are more closely related to economic and psychological factors rather than mere lineage incompatibility. Therefore, while kafaah nasabiyah may be a consideration in marriage, it is not a determinant factor in divorce mitigation. Instead, a more comprehensive, multidimensional approach is required. Penelitian ini mengkaji sejauh mana kafaah nasabiyah dapat menjadi solusi untuk memperkuat ketahanan rumah tangga di tengah meningkatnya kasus perceraian akibat kesenjangan sosial, ekonomi, dan budaya dalam masyarakat yang semakin heterogen. Penelitian ini menggunakan pendekatan kualitatif dengan desain penelitian kepustakaan. Data primer bersumber dari karya-karya Ibnu Qudamah, seperti al-Mughni, dan Ibnu Hazm melalui al-Muhalla, dilengkapi dengan data sekunder dari literatur fikih klasik dan kontemporer, dokumen-dokumen hukum Islam, dan analisis yurisprudensi di Indonesia. Teknik analisis data menggunakan metode deskriptif-analitis dengan pendekatan komparatif untuk mengidentifikasi persamaan dan perbedaan pemikiran kedua ulama dan implikasinya terhadap praktik hukum Islam di Indonesia. Temuan menunjukkan bahwa kafaah nasabiyah memiliki nilai historis dan sosiologis dalam menjaga stabilitas rumah tangga. Ibnu Qudamah mendukung konsep ini untuk mencegah ketidakharmonisan akibat kesenjangan sosial, sedangkan Ibnu Hazm menolaknya karena Islam tidak membatasi pernikahan berdasarkan garis keturunan.. Dalam konteks Indonesia, baik dalam lingkup pondok pesantren, madrasah, maupun program pendidikan pranikah, perspektif Ibnu Qudamah lebih banyak diadopsi dalam praktik sosial, terutama di masyarakat yang masih menjunjung tinggi stratifikasi berdasarkan garis keturunan dalam memilih pasangan pernikahan. Namun, penelitian ini juga menemukan bahwa penyebab utama perceraian di Indonesia lebih berkaitan erat dengan faktor ekonomi dan psikologis daripada ketidakcocokan nasab. Oleh karena itu, meskipun kafaah nasabiyah dapat menjadi pertimbangan dalam pernikahan, namun hal tersebut bukanlah faktor penentu dalam mengurangi perceraian. Sebaliknya, diperlukan pendekatan yang lebih komprehensif dan multidimensi.